Reconstruction of Vagina with Bilateral Pudendal Thigh Flap: A Solution for Atresia/ Agenesis of Vagina (TAJ: Journal of Teachers Association, 2023)
Reconstruction of vagina is a technically challenging surgery. The aim is to create a functionally and aesthetically satisfactory neovagina in a way that will be reliable and suitable for most  atients. Use of bilateral  udendal thigh fla  to create a neovagina may overthrow the conventional methods as there is no necessity for  osto erative dilation or vaginal intercourse to maintain adequate vaginal length and diameter. Vaginal reconstruction was done with bilateral  udendal thigh fla s, in seven  atients with vaginal agenesis, during 2 years, from July 2021 to June 2023. This method of vagino lasty is sim le, safe, and reliable and has shown satisfactory functional and cosmetic results. The reconstructed vagina has a natural angle and is sensate in its lower  art. No  osto erative stenting or dilatation is required. The donor site can be closed  rimarily and the scar is well hidden in the groin crease.TAJ 2023; 36: No-2: 11-16